Serum cholesterol and the progression of Parkinson's disease: results from DATATOP. - Xuemei Huang; Peggy Auinger; Shirley Eberly; David Oakes; Michael Schwarzschild; Alberto Ascherio; Richard Mailman; Honglei Chen; Parkinson Study Group DATATOP Investigators (PLoS ONE)
Background Recent studies have suggested that higher serum cholesterol may be associated with lower occurrence of Parkinson's disease (PD). This study is to test the hypothesis that higher serum cholesterol correlates with slower PD progression. Methods Baseline non-fasting serum total cholesterol was measured in 774 of the 800 subjects with early PD enrolled between 1987 and 1988 in the Deprenyl and Tocopherol Antioxidative Therapy of Parkinsonism (DATATOP) trial. Participants were followed for up to two years, with clinical disability requiring levodopa therapy as the primary endpoint. Hazard ratios (HRs) and 95% confidence intervals (CI) were determined for increasing serum cholesterol concentration (in quintiles) for clinical disability requiring levodopa therapy, after adjusting for confounders. At baseline, only nine subjects reported use of cholesterol-lowering agents (two with statins). Results The overall mean cholesterol level was 216 mg/dL (range 100-355). The HR of progressing to the primary endpoint decreased with increasing serum cholesterol concentrations. Compared to the lowest quintile, the HRs (95%CI), for each higher quintile (in ascending order) are 0.83 (0.59-1.16); 0.86 (0.61-1.20); 0.84 (0.60-1.18); and 0.75 (0.52-1.09). The HR for one standard deviation (SD) increase = 0.90 [(0.80-1.01), p for trend = 0.09]. This trend was found in males (HR per SD = 0.88 [(0.77-1.00), p for trend = 0.05], but not in females [HR = 1.03 (0.81-1.32)]. Conclusions This secondary analysis of the DATATOP trial provides preliminary evidence that higher total serum cholesterol concentrations may be associated with a modest slower clinical progression of PD, and this preliminary finding needs confirmation from larger prospective studies.